Mouth Dissolving Tablets: Bridging Laboratory Innovations and Consumer Convenience - Mishra, Kirtimaya; Jabeen, Asra; Vegesna, Swetha; Chintapalli, Gowri Sankar; Patra, Debasis; Jena, Diptimayee (International Journal of Pharmaceutical Investigation, 2026)
Mouth Dissolving Tablets (MDTs) are considered as a novel approach to improvize patient compliance and fast drug delivery. They constitute a significant improvement in pharmaceutical technology. The dissertation explores the numerous excipients used, their modes of action, and formulation strategies that are used to obtain the best bioavailability and dissolving rates. Key benefits are covered in detail, including speedier onset of action, better patient adherence, and simplicity of administration without the need for water. The overview also discusses the difficulties encountered in the development and manufacturing processes as well as the regulatory issues that are relevant to MDTs. MDTs are of the good hardness and dose uniformity variety that dissolve and dissolve quickly in our saliva in a couple of seconds. The fact that MDTs are administered without the need for chewing or water consumption is their most effective feature. Due to these unique qualities, this innovative dosage form is highly preferred by paediatric, geriatric, and most importantly travelling patients. Superdisintegrants, alike croscarmellose, crospovidone, sodium starch glycolate, and magnesium aluminium silicate (veegum HV) are required for the manufacture of this kind of tablet. In addition, methylcellulose is utilised as a bulking agent, mustard and soy lecithin as an emulsifying agent, fatty alcohol as a lubricant, and sweeteners and flavourings are added as additional ingredients in the MDT formulation.
Keywords: Patient Compliance; Fast Drug Delivery; Speedier onset of action; Hardness; Dose uniformity; Super disintegrants.